Correction of Post-traumatic Deformity of Lower Limb: A Case Report - Babu, Sufiyan; Bijukachhe, Binod (Grande Medical Journal, 2025)
Mal-union with leg length discrepancy is a known complication in open femoral shaft fractures, particularly when associated with vascular injury. Neglected conditions lead to further deformities due to soft tissue contractures which can cause significant disability with compromise in activities of daily living. Thorough history taking, clinical and radiological evaluation helps to identify the problems. Leg length discrepancy, bony deformities and soft tissue contractures can be effectively corrected through osteotomy, acute femoral lengthening and posteromedial release in single admission. Excellent functional outcome can be achieved cost-effectively in short duration.